Para além do acesso à moradia: uma avaliação do Programa "Minha Casa, Minha Vida" em Ituiutaba-MG - Jorge, Rafael Marchiori Silva Demetrio (2020)
The dissertation focuses on the theme inherent to the right to housing and, above all, on the national housing policy, highlighting the housing programs created by the federal government, especially “Minha Casa, Minha Vida” – PMCMV, which has generated significant effects in several Brazilian cities. In this case, it seeks to analyze the results of the nominated program in the municipality of Ituiutaba-MG. And although these programs play an important role in accessing housing, they still have problems and deficiencies in practice, notably in relation to the actions taken after the distribution and occupation of housing units. It should be noted that, in addition to the right to housing, policies also need to guarantee the population's access to public services, equipment for collective use, urban infrastructure and other aspects, or even so that they can experience the city more broadly. and collective in their daily practices, in the sense of also guaranteeing the right to the city. The methodological procedures were divided into some fundamental stages, aiming at the full development of the proposal, using qualitative research, interpreting the situation under investigation. The verification process was configured with the following research problem: do housing policies, when providing access to housing for the population, contemplate broader aspects of urban policy? Considering the most recent policy, as is the case with the PMCMV, is housing production being accompanied by other broader policies? Was access to housing followed by other actions? Or were past mistakes reproduced in relation to the production of these new housing developments? In relation to the general objective, it was constituted in the analysis of three housing estates implanted in Ituiutaba-MG by the “Minha Casa, Minha Vida” Program, considering not only access to housing but also urban infrastructure and public services, urban planning. Furthermore, the methodology adopted was based on bibliographic and documentary research. Data collection, in turn, was carried out in an observational, bibliographic, documentary and field manner. As for the main conclusions resulting from the study, it is noted that social and non-urban planning factors are capable of causing consequences for the non-implementation of housing policies. Still, those contemplated by the housing units resulting from the aforementioned program are, for the most part, satisfied with their residence, although they are notorious for not realizing the right to the city, socio-spatial segregation and, even, the periphery of part of the population, you need to travel long paths to certain points, including essential services.